2021
DOI: 10.3389/fnut.2021.647354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roasting on the Antioxidant Activity, Phenolic Composition, and Nutritional Quality of Pumpkin (Cucurbita pepo L.) Seeds

Abstract: In recent years, with the increasing awareness of health concerns and environment protection needs, there is a growing interest for consumers to choose plant-based food diets compared with those made from animal origin. Pumpkin seed is an excellent dietary source for protein, oil, and some essential micronutrients. Raw pumpkin seed may have a compromised flavor, color, as well as digestibility. Therefore, the objective of present study is to study the influence of roasting (120, 160, and 200°C for 10 min) on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 53 publications
3
17
0
Order By: Relevance
“…The TPC value decreased slightly (2.04 ± 0.11 mg GE/g) when germinated wheat was roasted at the highest temperature (188 • C) for 30 min (p > 0.001). Similar results demonstrating an increase in TPC values in the flours of grains and seeds at higher roasting temperatures have been reported in several studies [13,29,30]. Bound phenolic and flavonoid compounds are believed to be released during roasting due to destruction of the cell structure [30].…”
Section: Roasting Time-temperature Impact On Bioactive Compoundssupporting
confidence: 84%
See 1 more Smart Citation
“…The TPC value decreased slightly (2.04 ± 0.11 mg GE/g) when germinated wheat was roasted at the highest temperature (188 • C) for 30 min (p > 0.001). Similar results demonstrating an increase in TPC values in the flours of grains and seeds at higher roasting temperatures have been reported in several studies [13,29,30]. Bound phenolic and flavonoid compounds are believed to be released during roasting due to destruction of the cell structure [30].…”
Section: Roasting Time-temperature Impact On Bioactive Compoundssupporting
confidence: 84%
“…Similar results demonstrating an increase in TPC values in the flours of grains and seeds at higher roasting temperatures have been reported in several studies [13,29,30]. Bound phenolic and flavonoid compounds are believed to be released during roasting due to destruction of the cell structure [30]. However, oxidation and thermal degradation of phenolic compounds also leads to increased production of extractable phenolics upon heating [13,31].…”
Section: Roasting Time-temperature Impact On Bioactive Compoundssupporting
confidence: 83%
“…Pumpkin seed meal is the residue left after removing oil from it. It was reported to be a rich source of protein (>64%) and could be used as a functional food ingredient in the preparation of bakery, confectionary, extruded, and tailor‐made food products (Peng et al ., 2021). Therefore, the present study has been designed to improve the nutritional profile and functionality of pasta and to assess the effect of enrichment on the cooking quality and textural and structural characteristics of pasta.…”
Section: Introductionmentioning
confidence: 99%
“…mainly evaluated the correlation of phenolic contents and antioxidant parameters of PSO, which indicate that a linear relationship between DPPH• radical scavenging capacity and the content of total phenolic compounds, allowing antioxidant activity, increased proportionally with the phenolic contents. Other studies have suggested that the antioxidative activity correlates very well with the concentration of phenolics in PSO 91,95,96 …”
Section: Health Benefits Of Psomentioning
confidence: 86%